PEMBERDAYAAN MASYARAKAT MELALUI PROGAM WISATA - Dwi Cahyo Saputro (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2021)
n an era like now people will find high tourist attractctions, as evidenced by the hectic number ofCities and regions that support tourist attractions in their area, in order to increase the number of tourist whovisit as well as the spinning wheel of the economy in the area. In its promotion social media is an effective wayto attract tourist aspeceally young people who never break open their applications, both Instagram, Facebookand so on. An in Sidomukti Village, Kepohbaru Subdistrict, Bojonegoro Regency. There is a very good tourismpotential in the form of two reservoirs surrounded by teak trees and some vacant land around them which will beable to boost the economy of the surrounding community if later able to be realized as tourist attractions. Forthis reason, we strive to maximize the tourism potential of the village by coordinating and providing breakthroughs on the concept of tourisme in the future, in the form of layouts parks, orchards and some photo spotthat are loved by millennials. From these tourist attractions finally given the name “Sidomukti Park”. Thepurpose of the development activities of the “Sidomukti Park” is for the creation of a prosperous village troughthe utilization of the potential of the village into a tourist attraction which later on from this program will benefita lot, especially in terms of the economy of the surrounding community will also feel the impact, such as beingable to provide parking space, homestay and in terms of mind tenance can later work whit the surroundingcommunity especially youth organizatations. So that from this program there will be continuous communityempowerment for new innovations related to the “Sidomukti Park” tour. So in supporting the development ofthis four the method used in its development is a qualitative research method with a case study approach, thisresearch intens to provide a description of community empowerment trough the “Sidomukti Park” program andthe result of these activities is the exsistence of a concept related to tourism “Sidomukti Park” in the future, bothin terms of structuring to the program of community empowerment trough the tour. Proven for this year the tourreceived assistance in the form of fliying fox from the Departement of tourism, which will later beused to supportthe beauty of natural tourism.